UNPACKING TAG QUESTIONS IN ’THE OFFICE’: FREQUENCY, FUNCTIONALITY, AND COMEDIC FLAIR - Fatima Ghaffar; Muhammad Farukh Arslan; Muhammad Usman Bin Tariq (International Journal of Contemporary Issues in Social Sciences, 2024)
This study looks at the incidence and importance of tag questions in the dialogue of "The Office," a popular American comedy. Tag questions, which are short linguistic features affixed to assertions, play an important role in communication dynamics by requesting confirmation, conveying ambiguity, and allowing conversational flow. Despite their importance, tag questions have gotten little attention in scripted media situations, notably on television series. This research takes a mixed-methods approach, analyzing conversation transcripts from seasons one and two of "The Office." Data collection include gathering scripts from web sources, categorizing the corpus, and manually refining. The study finds that characters regularly use tag questions such "right?", "all right?", "yeah?", and "okay?" to verify, convey skepticism, and keep the discourse going. The findings show that tag questions add considerably to the comedy of "The Office" by punctuating jokes, underlining irony, and accentuating character peculiarities. This study contributes to our knowledge of language dynamics in scripted media by putting light on the pragmatic functions of tag questions and their significance in interpersonal communication in the setting of a popular comedy.